2012
DOI: 10.1161/circimaging.111.967554
|View full text |Cite
|
Sign up to set email alerts
|

Low-Flow, Low-Gradient Severe Aortic Stenosis Despite Normal Ejection Fraction Is Associated With Severe Left Ventricular Dysfunction as Assessed by Speckle-Tracking Echocardiography

Abstract: Background-Low-flow low-gradient (LFLG) is sometimes observed in severe aortic stenosis (AS) despite normal ejection fraction, but its frequency and mechanisms are still debated. We aimed to describe the characteristics of patients with LFLG AS and assess the presence of longitudinal left ventricular dysfunction in these patients. Methods and Results-In a multicenter prospective study, 340 consecutive patients with severe AS and normal ejection fraction were studied. Longitudinal left ventricular function was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
106
4
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(124 citation statements)
references
References 20 publications
8
106
4
6
Order By: Relevance
“…The prevalence of paradoxical LF/LG is thus much lower than reported in numerous previous studies (7-24%), 3,4,[7][8][9] and such discrepancy might be attributable to several factors, including differences in baseline characteristics of study populations and, in particular, AS severity, symptomatic…”
Section: Etiology and Prevalence Of Paradoxical Lf/lg Asmentioning
confidence: 60%
See 1 more Smart Citation
“…The prevalence of paradoxical LF/LG is thus much lower than reported in numerous previous studies (7-24%), 3,4,[7][8][9] and such discrepancy might be attributable to several factors, including differences in baseline characteristics of study populations and, in particular, AS severity, symptomatic…”
Section: Etiology and Prevalence Of Paradoxical Lf/lg Asmentioning
confidence: 60%
“…As reported in the original description of paradoxical LF/LG AS 4 and further confirmed in the present study, 6 this entity is most frequently characterized by restrictive physiology in relation to more pronounced LV concentric remodeling, reduced LV cavity size, impaired LV filling, and reduced systemic arterial compliance. Moreover, several studies 3,[7][8][9] have shown that longitudinal myocardial function is often impaired in these patients, thus reemphasizing that LVEF may underestimate the extent of LV systolic dysfunction in patients with LV concentric remodeling. Hence, the cutoff value of LVEF (<50%) proposed in the guidelines to define LV systolic dysfunction and eventually recommend AVR in patients with severe AS may have to be revisited (e.g., raised to 60%), or other more sensitive parameters, such as the global LV longitudinal strain, may have to be incorporated in the evaluation.…”
Section: Etiology and Prevalence Of Paradoxical Lf/lg Asmentioning
confidence: 99%
“…21,22 The sensitivity of these measures to alterations in deformation has resulted in their application, in both animal and human studies, to a variety of pathological conditions characterized by myocardial dysfunction despite preserved EF, including asymptomatic carriers of hypertrophic cardiomyopathy sarcomeric mutations, 23 Fabry's disease, 24 myocardial steatosis, 25,26 and rodent models of Duchenne muscular dystrophy. 27 Perhaps because of their less load-dependent nature, these measures have also proven informative in the setting of valvular heart disease in which alterations in loading conditions make EF a less reliable measure of contractile function, including severe aortic stenosis, 28 aortic regurgitation, 29 and mitral regurgitation. 30 In the case of coronary disease, global strain values obtained early after an acute myocardial infarction may effectively predict subsequent remodeling and functional recovery.…”
Section: Deformation Imaging As a Measure Of LV Function Detection Ofmentioning
confidence: 99%
“…sol ventrikül fonksiyonları, EF'den daha duyarlı olan, orta duvar yarıçap kısalma, boylamasına kısalma, yük-lenme oranı gibi parametrelerle daha geniş kapsamlı değerlendirildiğinde, subendokardiyal fibrozis gösteren bulgular elde edilebilir. [29] Bu hasta grubunun, paradoksal düşük akımı olmayan ciddi ve orta derecede aort darlığı olan hastalara göre daha kötü prognoza sahip olduğu da pek çok çalışmada gösterilmiştir. [7,30,31] Tanının doğru konulabilmesi ve uygun tedavinin seçilebilmesi için, paradoksal düşük akım ihtimali olan hastalarda, sol ventrikül çıkış yolu çapı, hız zaman eğrisi ve transvalvüler gradiyentlerin ölçüm ve kontrolleri tekrarlanmalıdır.…”
Section: Paradoksal Düşük Akımlı Hastalar Aşağıdakiunclassified